Smoothing sudden stops - Caballero, Ricardo; Krishnamurthy, Arvind; National Bureau of Economic Research (Cambridge, Mass. National Bureau of Economic Research, 2001)
Emerging economies are exposed to severe and sudden shortages of international financial resources. Yet domestic agents seem not to undertake enough precautions against these sudden stops. Following our previous work, we highlight in this paper the central role played by limited domestic development in ex-ante (insurance) and ex-post (spot) financial markets in generating this collective undervaluation of external resources and insurance. Within this structure, this paper studies several canonical policies to counteract the external underinsurance. We do this by first solving for the optimal mechanism given the constraints imposed by limited domestic financial development, and then considering the main - in terms of the model and practical relevance - implementations of this mechanism.
Keywords: Insurance exchages -- Mathematical models